2015
DOI: 10.1186/s12985-015-0388-z
|View full text |Cite
|
Sign up to set email alerts
|

Viral Etiology of acute respiratory tract infections in hospitalized children and adults in Shandong Province, China

Abstract: BackgroundThe dominant viral etiologies responsible for acute respiratory infections (ARIs) are poorly understood, particularly among hospitalized patients. Improved etiological insight is needed to improve clinical management and prevention of ARIs.MethodsClinical and demographic information and throat swabs were collected from 607 patients from 2011 to 2013 in Shandong Province, China. Multiplex RT-PCR (SeeplexTM RV detection, Seegene) was performed to detected 12 respiratory viral pathogens.ResultsA total o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
46
5
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 35 publications
(47 reference statements)
19
46
5
3
Order By: Relevance
“…In our previous study, increased numbers of influenza cases were reported during the rainy and winter seasons of Nepal [7]. Similar findings were reported in Shandong Province, China [11], Bhutan [12], Indonesia [13], and ailand [14].…”
Section: Discussionsupporting
confidence: 82%
“…In our previous study, increased numbers of influenza cases were reported during the rainy and winter seasons of Nepal [7]. Similar findings were reported in Shandong Province, China [11], Bhutan [12], Indonesia [13], and ailand [14].…”
Section: Discussionsupporting
confidence: 82%
“…Our data revealed a higher positive rate of total respiratory viruses 1617. As our hospital provides tertiary care, the disease severity of admitted children may be higher than other studies.…”
Section: Discussioncontrasting
confidence: 43%
“…Coinfections with different multiple viruses were reported in 15% to 61% of patients. [6][7][8][9]. Molecular techniques such as multiplex polymerase chain reaction (PCR) are widely used for the detection and identification of respiratory viruses [10][11][12] and are helpful in the management and treatment 2 BioMed Research International of respiratory infections [13].…”
Section: Introductionmentioning
confidence: 99%